2008
DOI: 10.2170/physiolsci.rp006208
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Modulation of GABAA Receptor Currents by Melatonin in Rat Gonadotropin-Releasing Hormone Neurons

Abstract: Gonadotropin-releasing hormone (GnRH) neurons represent the final output neurons in the central control of reproduction. γ-Amino butyric acid (GABA), one of the major regulators of GnRH neurons, depolarizes GnRH neurons isolated from adult rats via GABA A receptors. The presence of GABA A receptors in GnRH neurons has also been demonstrated morphologically. Furthermore, the pineal hormone melatonin is involved in the regulation of reproductive function, including the timing of the luteinizing hormone surge. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…These electrophysiological results clearly indicated the expression of functional MT1 as previously demonstrated by coexpression of MT1 and GABA A R in HEK293 cells [32], although the melatonin concentration is pharmacological. In our recent study [20], a significant modulation of the GABA A R currents was observed with 10 n M or higher concentrations of melatonin in endogenous GnRH neurons. Melatonin, however, tended to attenuate the currents in GT1–7 cells treated with vehicle alone.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These electrophysiological results clearly indicated the expression of functional MT1 as previously demonstrated by coexpression of MT1 and GABA A R in HEK293 cells [32], although the melatonin concentration is pharmacological. In our recent study [20], a significant modulation of the GABA A R currents was observed with 10 n M or higher concentrations of melatonin in endogenous GnRH neurons. Melatonin, however, tended to attenuate the currents in GT1–7 cells treated with vehicle alone.…”
Section: Discussionmentioning
confidence: 94%
“…We previously developed transgenic rats that express enhanced green fluorescent protein specifically in GnRH neurons under the GnRH promoter [17]. Using these animals, we analyzed several types of electrical activities in endogenous GnRH neurons [17,18,19,20,21]. We recently showed that melatonin modulates type-A γ-aminobutyric acid (GABA) receptor (GABA A R) currents in adult rat GnRH neurons in a sexually dimorphic manner [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct regulatory actions of melatonin on GnRH neurons are still unknown. Our previous study showed that melatonin directly modulates GABA A receptor currents in adult rat GnRH neurons in a sexually dimorphic manner [28]. In male GnRH neurons, melatonin augments the currents, suggesting a preferential expression of MT1, because MT1 and MT2 differentially modulate GABA A receptor functions [29].…”
Section: Discussionmentioning
confidence: 96%
“…GABA, GABA reseptör aracılığıyla GnRH nöronlarının uyarıla-bilirliğini etkilemekte ve melatoninin ise melatonin reseptör aracılığıyla bu uyarılabilirliği değiştirebilmektedir. [47] Ayrıca melatonin hormonunun LH dalgalanmasını içeren üreme işlevlerini düzenlenmesinde rol oynadığı bildirilmiştir. Valcavi ve arkadaşlarının yaptığı bir çalışmada melatoninin hormonunun büyüme hormonu (GH) salınımını GnRH'dan daha hızlı uyardığı bulunmuştur.…”
Section: Yaşlanma Ve Melatoninunclassified